The Uniform Data Set, Czech Version: Normative Data in Older Adults from an International Perspective - Nikolai, Tomas; Stepankova, Hana; Kopecek, Miloslav; Sulc, Zdenek; Vyhnalek, Martin; Bezdicek, Ondrej (Journal of Alzheimer's disease, 2018)
Outside of the United States, international perspectives on normative data for neuropsychological test performance, within diverse populations, have been scarce. The neuropsychological test battery from the Uniform Data Set (UDS) of the Alzheimer's Disease Centers (ADC) program of the United States National Institute on Aging (NIA) is one of the most sensitive batteries for the evaluation of both normal cognitive aging and pathological cognitive decline. This study aimed to determine the feasibility of the Czech Neuropsychological Test Battery from the Uniform Data Set (UDS-Cz 2.0), while also evaluating the results obtained from an international perspective. This paper describes data from 520 cognitively normal participants. Regression analyses were used to describe the influence of demographic variables on UDS-Cz test performance. Cognitive performance on all measures declined with age, with patient education level serving as a protective factor. Therefore, the present study provides normative data for the UDS-Cz, adjusted for the demographic variables of age and education. The present study determines the psychometric properties of the UDS-Cz and establishes normative values in the aging Czech population, which can be used in clinical settings.